The Watershed Line of the Distal Radius: Cadaveric and Imaging Study of Anatomical Landmarks - Bergsma, Minke; Doornberg, Job N.; Borghorst, Annelise; Kernkamp, W.A.; Jaarsma, R. L.; Bain, Gregory I. (Journal of Wrist Surgery, 2020)
Background Placement of volar plates remains a challenge as the watershed line may not be an easy-identifiable distinct line intraoperatively.Objectives The main objective of this article is to define how anatomical landmarks identifiable upon the volar surgical approach to the distal radius relate to the watershed line.Methods We identified anatomical landmarks macroscopically upon standard volar approach to the distal radius in 10 cadaveric forearms and marked these with radiostereometric analysis (RSA) beads in cadaveric wrists. The RSA beads were then referenced against the volar osseous structures using quantification of three-dimensional computed tomography and advanced imaging software.Results The mean measurements were the radial and ulnar prominences 11.1 mm and 2.1 mm proximal to the joint line of the distal radius, respectively. The interfossa sulcus was 0.3 mm proximal and 3 mm dorsal to the ulnar prominence. The watershed line was between 3.5 (minimal) and 7.6 (maximal) mm distal to the distal line of insertion of the pronator quadratus.Conclusion The watershed line is situated distal to the pronator quadratus, but with a wide variability making it an impractical landmark for plate position. The osseous ulnar prominence is a good anatomical reference for safe plate positioning, as it is located on the watershed line and easily palpated at surgery. One should keep in mind the sulcus—the point on the watershed line where the flexor pollicis longus runs—can be situated just proximal to the ulnar prominence.Clinical Relevance To provide anatomical landmarks that are easy to identify upon surgical approach without the direct need for intraoperative imaging.
Keywords: distal radius fracture; watershed line; volar approach; anatomy; Q3DCT imaging; volar plating